Tenancy reforms re-visited - Ashokvardhan, C (Mussoorie, 2000)
Author's interest in land reforms dates back to his training days, as an IAS probationer, at the LBSNAA (Lal Bahadur Shastri National Academy of Administration) Mussoorie, in 1980. Shri P. S. Appu, our Director, with all his fervour for land reforms, had endeavoured to ward off much of our initial cynicism about land reforms cynicism that had sneaked - somehow through general failure stories on the land reforms front, they, the freshers, had been carrying on the back of our mind.
Keywords: Tenancy act 1885; IAS as an author